Prediction of Mortlity Rate in Indonesia due to Covid-19 Using the Naïve Bayes Algorithm - Abdi Rahim Damanik; Dedy Hartama; Irfan Sudahri Damanik (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
One of the functions of this research is to obtain the latest information regarding the level of accuracy and death rates due to the Covid-19 pandemic. One of the tasks of planning a response to a pandemic is to access data related to the number of deaths due to Covid-19. The research that the author is carrying out will predict the death rate due to the COVID-19 pandemic in Indonesia. This study collects all data sourced from the website address https://sinta.ristekbrin.go.id/covid/datasets. By using Indonesia's death rate data due to covid-19 from March 2020 to July 2021. The calculation process and prediction workflow will use the Naïve Bayes Algorithm to be able to measure accuracy and predict the death rate due to the coronavirus in 2022. Prediction testing data figures with a total of 20 the area is in the highest class with a death rate of 120,568 cases obtained based on the calculation of the Naive Bayes algorithm, for an accuracy performance of 100% by testing using Rapidminer tools. It is hoped that the results of this prediction can be used by the government to overcome and set plans for good improvements to the community during the coronavirus pandemic.